Model Mitigasi Bencana Berbasis Multisensoris Untuk Anak Berkebutuhan Khusus Di SD Inklusi Kota Yogyakarta - Mahilda Dea Komalasari; Bayu Pamungkas (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2019)
The potential for earthquakes, floods, tornadoes in the city of Yogyakarta needs to be addressed with training and simulations for disaster mitigation efforts, especially for elementary school-aged children who are a group vulnerable to disasters and among them there are the most vulnerable groups, namely children with special needs ( crew). Children with special needs have the same rights as other children to know about how to protect and save themselves when a disaster occurs. Some of them have mobility barriers to carry out protection and even self-rescue independently. So it is necessary to have information on how the procedures/plans for rescue crews from disasters are needed. The training and simulations in this service activity aim to: (1) equip students and teachers with knowledge about the potential for earthquakes, floods, and tornadoes related to the condition of the area in the service area; (2) equip students and teachers with knowledge and attitudes in dealing with disasters; (3) equip students and teachers with knowledge about the importance of preserving the environment to prevent disasters; (4) providing alternative efforts to mitigate earthquakes, floods, and tornadoes based on multisensory disasters; and (5) train teachers to provide disaster mitigation assistance to students, especially children with special needs (ABK). This community partnership program is carried out by means of lectures, questions and answers, and demonstrations. Lecture and question and answer methods were carried out for socialization aimed at providing understanding to students about knowledge and attitudes in dealing with earthquakes, floods, and tornadoes, as well as socialization to explain the importance of environmental sustainability in order to prevent natural disasters, as well as socialization of geographic information related to potential disasters. in the city of Yogyakarta, as well as the concept of multisensory-based earthquake, flood and tornado disaster mitigation. Demonstration method for carrying out multisensory-based earthquake, flood and tornado disaster mitigation simulations. Partners in this community partnership program are SDN Karaganyar and SDN Minggiran. The two elementary schools are inclusive elementary schools located in the city of Yogyakarta. Based on observations at SDN Karanganyar and SDN Minggiran, there are students with special needs who do not understand how to protect and save themselves when a disaster occurs. Therefore, it is necessary to conduct disaster mitigation training to improve the ability to face multisensory-based disaster threats. The target in this community partnership program is ABK students at SDN Karanganyar and SDN Minggiran, and it was carried out from April 2018 to November 2018. Through training to increase the ability to face multisensory-based disaster threats, it is hoped that it can improve the ability of ABK students in dealing with disaster threats.